2021
DOI: 10.3389/fcimb.2021.748795
|View full text |Cite
|
Sign up to set email alerts
|

SOCS3 Promotes ALV-J Virus Replication via Inhibiting JAK2/STAT3 Phosphorylation During Infection

Abstract: Avian leukosis virus subgroup J (ALV-J) is an oncogenic retrovirus that causes immunosuppression and neoplastic diseases in poultry. Cytokine signal-transduction inhibitor molecule 3 (SOCS3) is an important negative regulator of the JAK2/STAT3 signaling pathway and plays certain roles in ALV-J infection. It is of significance to confirm the roles of SOCS3 in ALV-J infection and study how this gene affects ALV-J infection. In this study, we assessed the expression of the SOCS3 gene in vivo and in vitro, and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…SOCS3 is a critical negative regulator of the inflammatory response via JAK2/STAT3 activation 20,21 . Therefore, we measured the SOCS3 protein levels using western blot and investigated whether OCE could regulate SOCS3 production.…”
Section: Resultsmentioning
confidence: 99%
“…SOCS3 is a critical negative regulator of the inflammatory response via JAK2/STAT3 activation 20,21 . Therefore, we measured the SOCS3 protein levels using western blot and investigated whether OCE could regulate SOCS3 production.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, the JAK-STAT signaling pathway, closely related to leukemia and myeloid production, was activated after ALV infection [ 36 , 37 ]. Among the seven STATs with known functions, STAT3 plays a key role in the malignant transformation of cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, CIS may be an important factor that helps ALV-J evade the innate immune response in host. Similarly, it has recently been shown that ALV-J infection could inhibit the phosphorylation of the JAK2/STAT3 signaling pathway by upregulating the expression of SOCS3, which represses host innate immunity and facilitates viral replication ( 121 ). In addition to directly targeting negative regulators for interferon signal transduction pathways to achieve innate immune evasion, ALV-J can also suppress the expression of IFN by targeting host protein indirectly ( 122 , 123 ).…”
Section: Innate Immune Evasion By Avian Leukosis Virus (Alv)mentioning
confidence: 99%